Female and male obese Zucker rats display differential inflammatory mediator and long non-coding RNA profiles - Patel, Niketa A.; Lui, Ashley; Trujillo, Andrea N.; Motawe, Zeinab Y.; Bader, Deena; Schuster, Jane; Burgess, Andrea; Alves, Natascha G.; Jo, Michiko; Breslin, Jerome W. (Life sciences (1973), 2023)
The goal of this study was to identify mediators in peri-lymphatic adipose tissue (PLAT) that are altered in obese versus lean Zucker rats, with focus on potential sex differences MAIN METHODS: Mesenteric PLAT was analyzed with protein and lncRNA arrays. Additional RT-PCR confirmation was performed with epididymal/ovarian fat. MCP-1, TCK-1, Galectin-1, Galectin-3, and neuropilin-1 were elevated in PLAT from obese rats of both sexes. However, 11 additional proteins were elevated only in obese males while 24 different proteins were elevated in obese females. Profiling of lncRNAs revealed lean males have elevated levels of NEAT1, MALAT1 and GAS5 compared to lean females. NEAT1, MALAT1, and GAS5 were significantly reduced with obesity in males but not in females. Another lncRNA, HOTAIR, was higher in lean females compared to males, and its levels in females were reduced with obesity. Obese rats of both sexes had similar histologic findings of mesenteric macrophage crown-like structures and hepatocyte fat accumulation. While obese male and female Zucker rats both have increased inflammation, they have distinct signals. Future studies of the proteome and lncRNA landscape of obese males vs. females in various animal models and in human subjects are warranted to better guide development of therapeutics for obesity-induced inflammation.